ANALISIS KESULITAN SISWA MATERI BANGUN RUANG SISI DATAR BERDASARKAN TAHAP BERPIKIR VAN HIELE - Sahara, Raden Intan Ayu; Nurfauziah, Puji (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This study aims to determine the difficulties of students in solving the problem of polyhedron based on Van Hiele's thinking stages. The research method used is descriptive qualitative by giving essay test questions. The research subjects were 10 students from class IX E SMP Negeri 2 Cimahi. The results showed that 7 students were still at stage 0 (visualization), 2 students were at stage 1 (analysis) and only 1 person was at stage 2 or informal deduction. In this study, it was found that students who failed to reach the previous level would also fail to reach the next level. For stage 3 (deduction) and stage 4 (rigor) no student has been able to reach this stage. The factors that cause student difficulties are students still lacking the concept of polyhedron, unable to provide deductive conclusions and lack of skills and creativity from the concept of geometry in solving mathematical problems on polyhedron.